(untitled) (Fiep Bulletin - online, 2012)
Introduction: Atypical odontalgia (AO) is an orofacial neuropathic pain that affects thousands of people, applied to a tooth or tooth socket region, in the absence of any identifiable dental cause. It is a chronic condition, difficult to diagnose and is often treated wrongly. Materials and methods: We conducted a literature review regarding clinical features, diagnosis and treatment for AO with capsaicin. Discussion: The atypical toothache pain is constant, with characteristics of burning, stinging or pressure, no local presence of pathologies. The diagnosis is difficult because it is performed by exclusion. Capsaicin, which is the active component of chili peppers, is already used in treatments for other types of chronic pain as well as in the oral mucosa. Conclusion: The use of topical capsaicin is effective and should be considered for the treatment of AO, but they have side effects that may limit its use